2015
DOI: 10.1371/journal.pone.0145456
|View full text |Cite
|
Sign up to set email alerts
|

Nutrigenomic and Nutritional Analyses Reveal the Effects of Pelleted Feeds on Asian Seabass (Lates calcarifer)

Abstract: As nutrition-related expenses constitute the majority of the costs for aquaculture farms, it is essential for them to use feeds that provide an ideal combination of nutrients for the species of choice. In this study, the relative effect of consuming three different pelleted feeds (B, C and D) in comparison to frozen baitfish (A; control) were compared on juvenile Asian seabass (77.3 ± 22.4g) that were selected for increased growth rate over two generations. Our objectives were: 1) to evaluate the effects of di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 71 publications
1
20
0
1
Order By: Relevance
“…In this study, the functional characteristics of T. ovatus Fads6 , via heterologous expression in S. cerevisiae, indicated that the T. ovatus putative desaturase was Fads6 , with Δ4 desaturation activity. This was functionally similar to the Fads6 from Arabidopsis thaliana , Medicago truncatula , and Homo sapiens [12,13,14]. T. ovatus Fads6 exhibited low activity towards 22:4n-6 and 22:5n-3 substrates, such as 22:5n-6 (1.04%) and 22:6n-3 (39.29%).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…In this study, the functional characteristics of T. ovatus Fads6 , via heterologous expression in S. cerevisiae, indicated that the T. ovatus putative desaturase was Fads6 , with Δ4 desaturation activity. This was functionally similar to the Fads6 from Arabidopsis thaliana , Medicago truncatula , and Homo sapiens [12,13,14]. T. ovatus Fads6 exhibited low activity towards 22:4n-6 and 22:5n-3 substrates, such as 22:5n-6 (1.04%) and 22:6n-3 (39.29%).…”
Section: Discussionmentioning
confidence: 57%
“…Previous studies using yeast heterologous expression systems have indicated that Fads2 exhibits ∆6, ∆5, ∆4, and ∆8 activity in the biosynthetic pathway of LC-PUFAs [1,4,7,8,9,10,11]; however, little information on Fads6 has been reported. Ngoh et al (2015) [12] revealed that fads6 expression was detected to be underlying, and suitable as a bioindicator to identify wild and farmed Lates calcarifer [1,2]. Some studies stated that Fads6 is involved with lipid and fatty acid metabolism in Homo sapiens [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Lates calcarifer , a euryhaline carnivorous fish species commonly known as barramundi or Asian sea bass, is widely cultured throughout the Indo-Pacific region and Australia 1 , 2 . Currently, the commercial farming of this species is well established in ponds, net cages and recirculating aquaculture systems (RAS) in both fresh and saline water.…”
Section: Introductionmentioning
confidence: 99%
“…The Asian seabass ( Lates calcarifer ; Centropomidae ), also known as barramundi or giant perch, is an important food fish in many parts of the world ( Nelson, 2006 ; Vij et al, 2016 ; Vij et al, 2014 ). As such, there has been an increasing interest in its growth mechanism and nutritional needs in recent years, especially with a view to improve the production of good fillet of marketable quantity and quality ( Alhazzaa et al, 2011 ; Glencross et al, 2008 ; Katersky & Carter, 2009 ; Matthews et al, 1997 ; Ngoh et al, 2015 ; Srichanun et al, 2013 ; Tu et al, 2013 ; Xia et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, an increasing number of research projects and publications have been focusing on the Asian seabass ( Kuznetsova et al, 2014 ; Ngoh et al, 2015 ). Selection projects utilized the tools of molecular genetics to improve seabass lines ( Wang et al, 2011 ; Wang et al, 2006 ), transcriptomic studies have analyzed the genetic regulation of its sex change ( Ravi et al, 2014 ) or responses to a vaccine and bacterial infection ( Jiang et al, 2014 ) and others have investigated the evolution of the species ( Vij et al, 2016 ; Vij et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%